2011
DOI: 10.1109/lpt.2011.2113330
|View full text |Cite
|
Sign up to set email alerts
|

DPSK Signal Regeneration With a Dual-Pump Nondegenerate Phase-Sensitive Amplifier

Abstract: Abstract-We demonstrate, for the first time to our knowledge, regeneration of a 42.66 Gbit/s differential phase shift keyed signal using a dual-pump non-degenerate four wave mixing-based fiber optic parametric amplifier. The regenerative performance of the subsystem is characterized in terms of biterror-rate against narrow-band and wide-band introduced noise. Whilst a strong receiver sensitivity improvement, up to 20 dB, is noticed against narrow-band noise, against quasi-random (wideband) noise we observe a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, at the present time, the desirable regenerators for multilevel modulation formats are hardly available due to the difficulty in simultaneously deriving amplitude and phase regeneration regardless of a few schemes [4][5][6][7][8][9][10]. For example, the all-optical regeneration of DPSK can respectively be obtained by phase preserving limiter [5], amplitude regenerator with format conversion [6], nonlinear optical fiber loop mirror (NOLM) [7] or the phase sensitive amplifier (PSA) [8]. Multilevel amplitude regenerative structures based on NOLM and directional interference were theoretically proposed by Sorokina [9] and Hierold [10], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the present time, the desirable regenerators for multilevel modulation formats are hardly available due to the difficulty in simultaneously deriving amplitude and phase regeneration regardless of a few schemes [4][5][6][7][8][9][10]. For example, the all-optical regeneration of DPSK can respectively be obtained by phase preserving limiter [5], amplitude regenerator with format conversion [6], nonlinear optical fiber loop mirror (NOLM) [7] or the phase sensitive amplifier (PSA) [8]. Multilevel amplitude regenerative structures based on NOLM and directional interference were theoretically proposed by Sorokina [9] and Hierold [10], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This unique output property of PSA can be utilized for the phase stabilization or signal regeneration of the phase-modulated signal light. Various studies have reported PSA-based phase regeneration [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to cater for these developments, the modulation schemes should be shifted from amplitude-shift-keying (ASK) to phase shift keying (PSK) schemes, such as Binary Phase Shift Keying (BPSK), Differential Phase Shift Keying (DPSK), etc [3]. Moreover, most of the recently deployed high capacity systems are operating on phase modulation schemes [3], [4]. Because of this reasons the methods used for signal processing in amplitude modulation schemes will be no longer effective.…”
Section: Introductionmentioning
confidence: 99%
“…This research intends to show an attempt of carrier recovery. The relevant applications are phase synchronization for phase regeneration [3], [4], phase sensitive amplification [3], [7] and homodyne receivers [8], [9].…”
Section: Introductionmentioning
confidence: 99%